Diversity in psychiatry education and patient and public involvement: roundtable analysis - Miriam Stanyon; Nagina Khan; Analia Buckley; Naina Patel; Kirit Mistry; Karl Ryan; Subodh Dave (BJPsych Bulletin)
Patient involvement in psychiatry education struggles to be representative of the patients that doctors will treat once qualified. The issues of mental health stigma, cultural perspectives of mental health and the unique role of teaching, required exploring to establish the barriers and facilitators to increasing the diversity of patients involved in psychiatry education. To explore the causes of this lack of representation, a roundtable event with 34 delegates composed of people with lived experience of mental health issues, people from underserved communities, academics, mental health professionals and charity representatives met to discuss the barriers to involvement in psychiatry education and possible solutions. Themes were further developed in a context expert focus group. Notes from the roundtable and focus group were analysed and developed into recommendations for medical schools and mental health professional teaching departments.